Pengaruh Kompetensi Sosial dan Kompetensi Pisikologi terhadap Kinerja Karyawan pada Perusahaan PT BPRS Gubu Prima - Padillah, Riski; Firman, Dody (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the effect of social competence and psychological competence on employee performance at PT BPRS Gubu Prima. Social competence includes employees' ability to interact and cooperate with others, while psychological competence involves factors such as motivation, job satisfaction, and employee involvement in their work. The research method used was a survey using a questionnaire distributed to employees of PT BPRS Gubu Prima. The sample of this study consisted of 100 randomly selected employees. The collected data were analyzed using regression analysis to determine the relationship between social competence and psychological competence with employee performance. The results showed that both independent variables, namely social competence and psychological competence, have a significant influence on employee performance at PT BPRS Gubu Prima. Good social competence allows employees to communicate effectively and work together in teams, which in turn improves their performance. Meanwhile, high psychological competencies, such as strong motivation and high job satisfaction, are also positively related to employee performance.